New Baltic amber leafhoppers representing the oldest Aphrodinae and Megophthalminae (Hemiptera, Cicadellidae) - Dietrich, Christopher H.; Gonçalves, Ana Clara (European Journal of Taxonomy, 2014)
Three fossil leafhopper inclusions from Eocene Baltic amber, representing three new extinct genera and species, are described and illustrated. Eomegophthalmus lithuaniensis gen. et sp. nov. is tentatively placed in Megophthalminae, although it may represent the stem group from which Megophthalminae, Ulopinae, and Membracidae arose. Xestocephalites balticus gen. et sp. nov. and Brevaphrodella nigra gen. et sp. nov. are placed in Aphrodinae: Xestocephalini based on the structure of the head, leg chaetotaxy, and male genital capsule. These new genera and species represent the oldest known representatives of their respective subfamilies and the latter is the oldest known brachypterous adult leafhopper.